2012
DOI: 10.1111/j.1467-9477.2011.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

How does Intergroup Contact Generate Ethnic Tolerance? The Contact Hypothesis in a Scandinavian Context

Abstract: As European majority members are often hostile toward ethnic minorities, it is important to identify sources that reduce opposition to immigrants. First, focusing on Denmark, this article examines whether intergroup contact influences attitudes toward ethnic minority rights (henceforth: ‘ethnic tolerance’). Second, this study tests whether the contact‐tolerance relationship is mediated by self‐disclosure and symbolic threat. Furthermore, contact is measured as workplace contact in order to reduce self‐selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…This finding indicates that when it comes to the impact of sectarianism on attitudes towards other minorities, Northern Ireland is indeed still a special case. Consistent with other research and with findings on other countries (McLaren 2003;Hayes and Dowds 2006;Hewstone et al 2006;Tam et al 2007;Frølund Thomsen 2012;McKee 2015), we found that regular contact (at least once a week) with minorities makes individuals less likely to endorse negative attitudes towards them. The findings support contact theory (Pettigrew 1998;Brown and Hewstone 2005;Tam et al 2009).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This finding indicates that when it comes to the impact of sectarianism on attitudes towards other minorities, Northern Ireland is indeed still a special case. Consistent with other research and with findings on other countries (McLaren 2003;Hayes and Dowds 2006;Hewstone et al 2006;Tam et al 2007;Frølund Thomsen 2012;McKee 2015), we found that regular contact (at least once a week) with minorities makes individuals less likely to endorse negative attitudes towards them. The findings support contact theory (Pettigrew 1998;Brown and Hewstone 2005;Tam et al 2009).…”
Section: Resultssupporting
confidence: 92%
“…Another finding which indirectly supports contact theory (McLaren 2003;Hayes and Dowds 2006;Hewstone et al 2006;Frølund Thomsen 2012) is that having attended a religiously mixed (as opposed to segregated) secondary school is statistically negatively related to negativity towards immigrants. Thus, enhanced contact with the religious "other" in school makes people more likely to be tolerant of the religious "other" and towards other outgroups.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Sijuwade (2011) specifically assessed multivariate predictors of tolerance among ethnic, including gender, marital status, religiosity, income, occupation, and education. Other indicators such as inter-ethnic marriage, friendship, entertainment forms (Sijuwade, 2011), workplace (Thomsen, 2012), ethnic demography, conscious and unconsciousness (Bambulyakа, 2011), societal status (Bettelheim & Janowitz, 1949), social network and voluntary association (Cote & Erickson, 2009) and political competition (Kasara, 2013) are also often regarded as tests of ethnic tolerance with a mixture of end result. Studies also found that education, ranging from moderate to strong, contributes to tolerance measures (Statistics New Zealand, 2011) but was reported vice versa in Malaysia (Najeemah, 2006;Yasmin & Najeemah, 2010).…”
Section: Introductionmentioning
confidence: 99%